If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(h) = 35h + 215 Multiply F * h hF = 35h + 215 Reorder the terms: hF = 215 + 35h Solving hF = 215 + 35h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-35h' to each side of the equation. -35h + hF = 215 + 35h + -35h Combine like terms: 35h + -35h = 0 -35h + hF = 215 + 0 -35h + hF = 215 Reorder the terms: -215 + -35h + hF = 215 + -215 Combine like terms: 215 + -215 = 0 -215 + -35h + hF = 0 The solution to this equation could not be determined.
| 4x+1+4x+4=89 | | 13-x-x=27 | | 8x-4-4x=2x+4 | | 3/4x+4=5/6x | | x^6-4x^3+3=0 | | 7+5x+2x-14=-21 | | 2x-8=-8+2x | | 2x+10=8x-1 | | 2x+1=3x-31 | | 3x/8+1=x/3-1/2 | | 25x-9=50x+11 | | 6x-(x-10)=-15 | | -12/(6/5x) | | 14x+1+4-2+2=89 | | -12/6/5x | | 9w+3=7w | | -3-8(6-8x)=-109 | | 7x-3(x+4)=-16 | | -x/2=26 | | -8x+9=-31 | | 6x+4=4x-26 | | .25x-.375x=2 | | 7y+12=5y-2 | | 6x+4+4x=-26 | | 4n+(7+n)=52 | | x+2*x-4=0 | | n--12=8 | | A-10a | | 1+3x/8*6= | | 11n+6=n-44 | | 4-3.2=14 | | -35=b-34 |